HUBUNGAN GRIT DAN RESILIENSI AKADEMIK KELAS X AB DI SMK NEGERI 2 JEMBER TAHUN AJARAN 2021/2022 - Arifin Nur Budiono; Elok Roudhotul Izzah; Fakhruddin Mutakin (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The Relationship between Grit and Academic Resilience Class X AB at SMK Negeri 2 Jember Academic Year 2021/2022. This research is about the relationship between grit and academic resilience of class X AB at SMK Negeri 2 Jember with 32 students out of 32 students who were taken as a whole using a saturated sample. The method used in this study is the questionnaire method. Data analysis using the correlation coefficient formula by looking for the r product moment. Based on the research results, it can be explained that the product moment correlation analysis obtained an rcount of 0.704. As for the rtable calculation, it shows a correlation value of 0.704 with a total of 32 N. It can be seen that the rcount and rtable values are at a strong degree. Namely, both show a correlation value of 0.704. This means that these two variables are correlated which shows the degree of strong relationship with a positive form of correlation. Thus the conclusion is obtained: There is a relationship between grit and academic resilience of class X AB at SMK Negeri 2 Jember for the 2021/2022 academic year and the results of this correlation are strong. In this thesis also provides suggestions for the perfection of further research and closing is the end of the research report of this thesis.